The Dairy Productivity Of Camels Depends On Their Species - Tleumuratov A .K; Sitirzayev S.T; Erniyazov A.Q; Tilepbergenov A.O (Global Scientific Publishing, 2024)
This article provides information on the milk yield of camels depending on their species, as well as the chemical composition of the milk produced during lactation.
Keywords: Dromedary camels; Bactrian camels; milk yield